Institutional performance of the Amil Zakat Institution in Palembang City: National Zakat Index approach - Fera Widyanata; Noraini Nasirun; Media Kusumawardani (Universitas Negeri Surabaya, 2022)
The previous studies in Indonesia showed the results of various zakat performances among Zakat Institutions (LAZ) using the National Zakat Index (NZI) method. This study aims to analyse the institutional performance of LAZ in Palembang City more precisely in managing Zakat, Infaq and Sodaqoh (ZIS) still by using the National Zakat Index (NZI) method but specifically for the analysis of institutional performance. Four methods of measuring the micro variables of IZN's institutional performance are collection, management, distribution, and reporting. The data were collected from the registered LAZs in Palembang City through the assessments of the institutional reports. Three LAZs are qualified with the criteria involved in this study: Yatim Mandiri, Dompet Dhuafa and Yakesma. This result provides an institutional performance indicator for LAZs in Palembang City, where Dompet Dhuafa achieved an excellent category while Yakesma and Yatim Mandiri reached a good category. All LAZs excel in the productive economy and social programs (education and humanity). At the same time, Dompet Dhuafa and Yakesma are excellent at collecting, managing and da'wah (preaching) programs. Meanwhile, Yatim Mandiri achieves its excellence in management and reporting aspects. It is concluded that BAZNAS Palembang increase the number of officially registered LAZs to increase professionalism and transparency in the distribution of ZIS and increase public trust.